Kinetics of oil generation from brackish-lacustrine source rocks in the southern Bohai Sea, East China. (January 2020) - Liang, Haoran; Xu, Fanghao; Grice, Kliti; Xu, Guosheng; Holman, Alex; Hopper, Peter; Fu, Deliang; Yu, Qing; Liang, Jiaju; Wang, Deying
Highlights: Confined pyrolysis was performed on three Type II brackish-lacustrine mudstones. These show similar paleoenvironment, chemical composition, kinetics and TR curves. Kinetic model of oil (C14+ ) generation of brackish-lacustrine kerogen was established. Oil generation window of brackish-lacustrine kerogen was 92–137 °C under 3 K/Ma. Abstract: Oil generation (C14+ hydrocarbons) of three Type II kerogen samples isolated from brackish-lacustrine mudstones from Palaeogene strata (Ed3, Es1, Es3 ) in the southern Bohai Sea was simulated by closed-system gold tube experiments. In addition, a series of complementary analyses (Rock-Eval pyrolysis, total organic carbon, vitrinite reflectance, trace element, X-ray diffraction and flash pyrolysis-gas chromatography–mass spectrometry) were also performed to identify the bulk geochemistry, palaeo-environment and chemical composition of the kerogen. The aim of this study was to achieve a better understanding of the kinetics of oil generation from lacustrine source rocks in the southern Bohai Sea. The results show that the three samples are Type II source rocks deposited in similar palaeo-environments (hot and arid climates, anoxic conditions, and brackish water in shallow to semi-deep lakes) with consequent similarity in the chemical compositions of their kerogens. The organic matter inputs are predominantly composed of lacustrine microalgae, with a relatively small contribution from land plants. The activation energies of oil generation from these samples show a range of 44–52 kcal/mol, with a frequency factor varying from 1.116 × 10 14 to 1.274 × 10 14 s −1 . Due to the similar palaeo-environments and chemical composition, samples in this study exhibit strong consistencies in kinetic parameters. Transformation ratio (TR) evolution curves of oil generation from the three samples, calculated under a linear heating rate (3 K/Ma), exhibit a slight difference, which varies within 4 °C at a given TR. Due to the great similarities of the three kinetic models, an average kinetic model for the Type II brackish-lacustrine source rocks in the southern Bohai Sea was established. This model integrates the characteristics of the three kinetic models and is still dominated by activation energy of 52 kcal/mol. The geological temperature of the oil generation phase for the average model in the southern Bohai Sea is from 92 to 137 °C.